The Expression of the North/South Conflict in Great Day in the Morning (Jacques Tourneur, 1956): Western Conventions and Southern Motifs, Subversion and Satire - Gilles Menegaldo (Revue LISA)
Great Day in the Morning is among the few Westerns to deal with the Civil War as it was actually taking place. Tourneur’s film offers an example of generic hybridity, associating the codes of the Western and numerous references to Southern culture. The French-born director subverts a number of conventions of the genre, going against expectations and presenting rather ambiguous or ambivalent characters. Night scenes are numerous and Tourneur uses lights and shadows to convey these ambiguities. To some extent, the protagonist Owen Pentecost coming from North Carolina embodies the charm and charisma of the Southern gentleman, but he also acts like a Southern rogue in some circumstances. At first in a position of power, he gradually loses control over the situation when the war breaks out, but manages to save the gold for the Southern Cause that he eventually embraces. As in many films set in the South, women play a prominent part and they do show great energy, resilience and resistance to male authority. The rivalry between Ann Alaine and Boston Grant constitutes an important narrative thread in a context of war between two factions. The film uses some tropes of the Southern to confront two cultures with a satirical intent. Tourneur does exploit, with a tinge of irony, a romanticized vision of Southern culture, denouncing the hypocrisy and fanaticism of the Unionists while he emphasizes the idealistic stance of the Southerners.